2020
DOI: 10.1021/acs.est.0c03331
|View full text |Cite
|
Sign up to set email alerts
|

pH Dependence of the OH Reactivity of Organic Acids in the Aqueous Phase

Abstract: Photochemical processing taking place in atmospheric aqueous phases serves as both a source and a sink of organic compounds. In aqueous environments, acid–base chemistry and, by extension, aqueous-phase pH, are an important yet often neglected factors to consider when investigating the kinetics of organic compounds. We have investigated the aqueous-phase OH-oxidation of pinic acid, cis-pinonic acid, limononic acid, and formic acid (FA) as a function of pH. We have also extended our studies to other organic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(67 citation statements)
references
References 53 publications
(121 reference statements)
4
59
4
Order By: Relevance
“…Thus, in the absence of buffering, or a chemical OH − source compensating for acidification, less acidic or even slightly basic particles are rapidly acidified in the troposphere. This is also known for freshly formed sea salt particles, which rapidly become acidified within minutes after their emission, characterized by a pH drop by about 4 pH units (Angle et al, 2021). Furthermore, Fig.…”
Section: Acidity and Sulfur Oxidationmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, in the absence of buffering, or a chemical OH − source compensating for acidification, less acidic or even slightly basic particles are rapidly acidified in the troposphere. This is also known for freshly formed sea salt particles, which rapidly become acidified within minutes after their emission, characterized by a pH drop by about 4 pH units (Angle et al, 2021). Furthermore, Fig.…”
Section: Acidity and Sulfur Oxidationmentioning
confidence: 62%
“…Therefore, the statements of Zhao et al (2016), regarding the pH dependence in the reactivity of saturated carboxylic acids, are by far too overgeneralized. For the sake of completeness, a more recent study by the same authors (Amorim et al, 2020) shows that larger organic acids indeed do not exhibit much pH dependence.…”
Section: Oh Radical Oxidationsmentioning
confidence: 94%
“…Amorim et al and Ervens et al suggested that smaller alkyl groups normally show a stronger deprotonation dependence on the ·OH reactivity by up to 1 order of magnitude higher compared to larger alkyl groups. Larger alkyl groups provide more H atoms for abstraction and reduce the electronic effect of the deprotonation from the carboxyl groups …”
Section: Resultsmentioning
confidence: 99%
“…Although the rate constants used differ slightly from the compiled rate constants in Table S3, the variation trends of the ratios as a function of the carbon chain length are constant. Amorim et al 50 and Ervens et al 19 suggested that smaller alkyl groups normally show a stronger deprotonation dependence on the •OH reactivity by up to 1 order of magnitude higher compared to larger alkyl groups. Larger alkyl groups provide more H atoms for abstraction and reduce the electronic effect of the deprotonation from the carboxyl groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation